MRI: an update and review on bio-effects and safety considerations - Kaur, Amarinder; Dhillon, Naureen; Singh, Simarpreet; Gambhir, Ramandeep Singh (International Journal of Research in Medical Sciences, 2017)
Diagnostic imaging technologies such as magnetic resonance (MR) are vital to catching signs of disease early and high quality diagnosis for treatment planning. However, some patients are unable to take advantage of its life saving capabilities. The procedures can be claustrophobic and the contraindications of MRI in patients having implants, pacemakers and also the risks associated with the use of cryogens, contrast agents etc. So this article provides an update on review on the bio effects and safety considerations for both patient and health practitioner with respect to the use of clinical MRI.